Case Report On Omphalocele - Mr. Pranay Wankhede, Ms Darshana Kumari (Drugs and Cell Therapies in Hematology, 2021)
Omphalocele is a type of congenital anomaly in which the infant’s intestines and other organs of abdomen is surrounded with translucent sac, which can be rarely broken. As this birth defect is protruded outside the navel, hence it is also referred to as exomphalos. Omphalocele affects about one in every 3500 births, however half of the babies born with the disorder are stillborn. Patient Details: A 2.6 Kg male child was born to a G3P1L1A1 mother at 37 weeks of gestational age via Lower Segment Caesarean Section on 27/05/21 at 3:30 PM. The baby cried immediately after birth, but it was noticed to have a protrusion over the umbilicus for which the baby was referred to AVBRH for further management. Diagnostic Evaluation: HB= 19.4 gm%, TLC= 22900/cumm, PLT= 2.62 lakhs/cumm. USG of abdomen revealed Omphalocele with intestine as content. Therapeutic Intervention: The physicians scheduled operation a day after the admission of the patient, thereby keeping him nil by mouth and starting intravenous fluids. Further, the patient was taken on Continuous Positive Airway Pressure along with intubation on pressure control mode of ventilation. Conclusion: My patient being a new-born male child was admitted to Paediatric Ward No – 22, of AVBRH on 27/05/2021 for the treatment of protrusion of the abdomen which was later diagnosed as Omphalocele. The patient underwent Omphalocele repair surgery on 28/05/2021. After taking proper interventions, the patient’s condition showed improvement and has been discharged on 08/06/2021.